Penerapan Akuntansi Sederhana pada Pembuatan Laporan Keuangan Mesjid Al-Muttaqin di Lembang Kabupaten Bandung Barat - Bramasto, Ari; Soetiman, Enang Narlan; Surtikanti (Jurnal Pengabdian Tri Bhakti, 2022)
Mosque: Al-Muttaqin in, Lembang District, West Bandung, West Java 40391, is one of the mosques in the West Bandung Regency area and in general the mosque moves to serve the needs of the general public in terms of worship. preparation of financial reports and do not yet have the means of a simple accounting program, and need assistance to prepare financial reports. The implementation of community service is willing to try to make simple mosque financial reports with the Excel application